3.3.2. Synthesis, crystal structure and biological activity of 1-(phthalazin-1(2H)-one)[(Pyridin-2-yl)ethylidene]hydrazone and its cobalt (III) complex (Communications in Inorganic Synthesis, 2015)
A new mononuclear complex of cobalt (III) (2) with 1-(phthalazin-1(2H)-one)[(Pyridin-2-yl) ethylidene] hydrazone ligand (1) has been synthesized and characterized by elemental analysis, IR and mass spectroscopic techniques. The crystal structures of the free ligand (1) and its complex (2) have been determined by single crystal X-ray diffraction technique. In complex 2 the hydrazone ligand chelates to the cobalt (III) ion through nitrogen atoms in a tridentate manner, giving an octahedral geometry where the cobalt (II) was oxidized to cobalt (III). The antifungal activity of ligand 1 and its complex 2 was studied against Aspergillus niger, Aspergillus flavus and Candida albicans. The results revealed modest activity of complex 2 against the tested organism with inhibition zones of 14, 15 and 14 mm, compared to the free ligand 1 with the inhibition zones of 12, 11 and 12 mm for A. niger, A. flavus, C. albicans respectively.